Membangun Kesadaran Lingkungan Pada Remaja Di Asrama St. Angela Sedayu - Fridayani, Januari Ayu; Istono, Minta; Puri, Anindita Dewangga (Pakis Journal Institute, 2024)
The community service program aimed at raising environmental awareness among the youth at St. Angela Sedayu Girls' Dormitory was conducted through three main phases: initial observation, outreach, and evaluation. The outreach provided education on environmental management, energy conservation, as well as the concepts of sustainable food consumption and slow fashion. This approach was supported by the moral and spiritual values from the encyclical Laudato Si', which emphasizes the importance of caring for the earth as our